Carbon nanofiber with selectively decorated pt both on inner and outer walls as an efficient electrocatalyst for fuel cell applications - Balan, Beena K.; Unni, SreeKuttan M.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2009)
A novel electrocatalyst, with excellent Pi dispersion oil the inner and outer wall of a carbon nanofiber (CNF) was prepared by a modified polyol process in which both surface tension and polarity characteristics of the medium were properly adjusted to favor solution entry into the tubular region by capillary filling and homogeneous wetting of the inner wall surface by the solvents. The pristine CNF, which possesses an inherently active inner wall surface and inactive outer Wall surface, led to selective Pt deposition along the inner wall, whereas activation of the outer wall with chemical functionalization resulted in excellent dispersion of Pt along both inner and outer walls. Structural and morphological characterizations using high resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD) revealed that when Pt could be dispersed along the inner as well as the Outer walls of CNF, the Pt particle size decreased to almost half as compared to the one With Pt decoration only along a single wall of the Substrate material. Further, electrochemical studies using cyclic voltammetry (CV) and rotating disk electrode (RDE) measurements revealed enhanced methanol oxidation and oxygen reduction properties, respectively. The electrochemical active area obtained for the catalyst with both inner and outer wall Pt decoration wits nearly two times higher than that corresponding to the one with only inner wall Pt decoration. Similarly, the rate constant for the oxygen reduction reaction displayed by this sample was four times higher in comparison with the sample prepared by Utilizing only one wall for Pt decoration.

High pt utilization electrodes for polymer electrolyte membrane fuel cells by dispersing pt particles formed by a preprecipitation method on carbon ``polished'' with polypyrrole - Unni, SreeKuttan M.; Dhavale, Vishal M.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2010)
Pt utilization on carbon black (CB) has been significantly improved by initially utilizing polypyrrole (PPy) as a moiety to ``polish'' the carbon surface and subsequently by dispersing Pt particles formed by a preprecipitation process to minimize their migration into the geometrically restricted areas of the carbon surface. This process strategy has helped to significantly extend the triple-phase boundary as a greater number of Pt particles comes in direct contact with Nafion, leading to a substantial improvement in the overall catalyst utilization. Preliminary analyses such as IR, thermogravimetric analysis, and N(2) sorption confirmed the presence of PPy on the surface. Approximately 50% reduction in the surface area of CB after the controlled in situ polymerization of pyrrole monomer on the carbon surface indicated preferential filling and coverage of pores and other geometrically restricted pockets of carbon surface. On the other hand, by converting Pt into colloids in the preprecipitation method prior to their reduction, the platinum particles are forced to stay on the hybrid support; a major part of which otherwise would have been migrated into the surface pores and defect sites. Platinum particle size on these hybrid supports is 2 times higher than the catalyst prepared by polyol process. However, the electroactive surface area and mass activity are 2 times higher than that of the Pt particles prepared by polyol on hybrid material and are also significantly higher than that of the conventional electrocatalysts prepared by the polyol method. At 0.8 V, the kinetic current density (j(k)) of Pt/C-PPy-Pre obtained from the Koutecky-Levich plot is 1.5 and 2.5 times higher than that of catalysts prepared by the polyol method on PPy-coated carbon and Vulcan XC-72 carbon, respectively. Almost 210 and 160 mW cm(-2) improvement for the maximum power density, respectively with oxygen and air, was obtained with the modified system in comparison to the conventional system when the single cell evaluations were carried out at 60 degrees C with a Pt loading of 0.5 mg cm(-2) in the anode and cathode sides. This enhancement in the cell performance under the two different oxygen partial pressure conditions clearly emphasizes the improved oxygen reduction reaction (ORR) and mass-transfer characteristics of the hybrid electrode material compared to the other catalysts.

Pt-MoOx-carbon nanotube redox couple based electrocatalyst as a potential partner with polybenzimidazole membrane for high temperature polymer electrolyte membrane fuel cell applications - Vellacheri, Ranjith; Unni, SreeKuttan M.; Nahire, Sandip; Kharul, Ulhas K.; Kurungot, Sreekumar (Electrochimica Acta, 2010)
A redox couple based electrocatalyst comprising of Pt-Multi Wall Carbon NanoTube (Pt-MWCNT) promoted with molybdenum oxide (MoOx, 2 < x < 3) nanoparticles was prepared. The objective was to effectively organize the Pt-MoOx interface on the smooth MWCNT surface to overcome the practical difficulties associated with establishing such interface with Pt dispersed on carbon morphologies possessing surface irregularities. The present study revealed the importance of stringent controlling of the additive level for maintaining a balanced bifunctional behavior of the catalyst combination through the synergistic effects by the components and the need of a proton conducting membrane operable at high temperature to get better output from the Polymer Electrolyte Membrane Fuel Cell (PEMFC) systems. An indigenously developed polybenzimidazole (PBI) membrane was used to fabricate a membrane electrode assembly (MEA) as it can be operated at higher temperatures compared to that of Nafion membranes. MoOx additive level was carefully controlled by monitoring the active Pt area by cyclic voltammetry. All prepared electrocatalysts were characterized by using HRTEM, XRD and XPS to get information on dispersion and morphology, crystalinity and oxidation state of different elements, respectively. The system prepared with 5% MoOx addition with respect to Pt (hereafter Pt-MoOx(5%)-MWCNT) displayed balanced active Pt area and excellent oxygen reduction reaction (ORR) and methanol oxidation reaction (MOR) activities. Rotating Disk Electrode (ROE) system was extensively utilized to understand the ORR kinetics and the favorable role of MoOx as the promoter in the reaction. The kinetic current (j(k)) measured at 0.02 V vs. Hg/Hg2SO4 electrode from the Koutecky-Levich plots was 9 times higher and the apparent activation energy during single cell evaluation was 27 kJ/mol lower for the MoOx promoted system, compared to the system without the additive. A higher operating temperature significantly favored the cell performance by a combined effect of enhancement in proton conductivity of the PBI membrane and possible kinetic benefit by the well postulated oxygen spill over effect by the MoOx type systems in some combinations involving such systems. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Methanol oxidation reaction; MWCNT; oxygen reduction reaction; PBI membrane; PEMFC

Ex-situ dispersion of core-shell nanoparticles of Cu-Pt on an in situ modified carbon surface and their enhanced electrocatalytic activities - Dhavale, Vishal M.; Unni, SreeKuttan M.; Kagalwala, Husain N.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Chemical Communications, 2011)
Direct dispersion of core-shell nanoparticles on a carbon support (Cu@ Pt/C) has been achieved while retaining the essential core-shell features of the nanoparticles by adopting an in situ surface modification-cum-anchoring strategy.

Disordered brownmillerite Ba2InCeO5+delta with enhanced oxygen reduction activity - Jijil, Chamundi P.; Unni, SreeKuttan M.; Sreekumar, Kurungot; Devi, R. Nandini (Chemistry of Materials, 2012)
A disordered brownmillerite, Ba2InCeO5+delta, with slight tetragonal distortion from ideal cubic perovskite is synthesized and its oxygen reduction reactivity tested. The material displayed oxygen reduction behavior in alkaline solution comparable to that of standard 40 wt % Pt/C catalyst and attractive activity characteristics which renders it a potential system for low temperature fuel cell applications.
Keywords: brownmillerite; fuel cell; oxygen reduction reaction; Rietveld refinement

Graphene enriched with pyrrolic coordination of the doped nitrogen as an efficient metal-free electrocatalyst for oxygen reduction - Unni, SreeKuttan M.; Devulapally, Saikrishna; Karjule, Neeta; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
We report an efficient template-free synthetic route for the preparation of mesoporous nitrogen-doped graphene (NGE) containing a high weight percentage of pyrrolic nitrogen, good specific surface area and comparable electrochemical oxygen reduction activity as that of the state-of-the-art 40 wt% Pt/C catalyst. The desired coordination of nitrogen in the carbon framework of graphene has been conceived by a mutually assisted redox reaction between graphene oxide (GO) and pyrrole, followed by thermal treatment at elevated temperatures. NGE exhibits a high surface area of 528 m(2) g(-1) and a pore diameter of similar to 3 to 7 nm. The heat treatment temperature plays a pivotal role in establishing the desired pyrrolic coordination of nitrogen in graphene for the electrochemical oxygen reduction reaction. The NGE sample obtained after heat treatment at 1000 degrees C (NGE-1000) has 53% pyrrolic nitrogen content compared to the similar samples prepared by treating at low temperatures. Most importantly, NGE-1000 has displayed a significantly low overpotential for oxygen reduction with the onset potential very closely matching that of the commercial 40 wt% Pt/C. It is noteworthy that the reaction involves the desired 4 electron transfer as observed in the case of the Pt based electrocatalysts, leading to a significantly high kinetic current density of 6 mA cm(-2) at -0.2 V. Moreover, the fuel tolerance and durability under the electrochemical environment of the NGE catalyst is found to be superior to the Pt/C catalyst.

1-Dimensional confinement of porous polyethylenedioxythiophene using carbon nanofibers as a solid template: an efficient charge storage material with improved capacitance retention and cycle stability - Anothumakkool, Bihag; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Kurungot, Sreekumar (RSC Advances, 2013)
Here, we report a highly conducting porous 1-dimensionally (1-D) confined nano hybrid of polyethylenedioxythiophene (PEDOT) using a cup-stacked hollow carbon nanofiber (CNF) as a solid template for potential charge storage applications. The unique features of the nano confinement involve significantly high porosity and conductivity with the establishment of the 1-D architecture. Since the tubular morphology of the CNF with its open tips provides facile routes for the electrolyte, the overall utilization of the active surface and conductivity increases the charge storage properties of PEDOT in the hybrid. The approach helped in achieving a high specific capacitance of 177 F g(-1) for 40% PEDOT-CNF at a scan rate of 50 mV s(-1) and in retaining 130 F g(-1) even at 3000 mV s(-1) compared to 76 and 30 F g(-1) respectively given by pure PEDOT in 0.5 M H2SO4. The hybrid CP-40 shows a very high power density of 51 kW kg(-1) with an energy density of 4.7 Wh kg(-1). High capacitance retention is supported by the low charge transfer resistance and very low time constant (less than 0.5 s) values for the hybrid using impedance analysis. Phase angle calculations from a Bode plot also show an ideal capacitive nature with -90 degrees phase difference at 0.1 Hz for the hybrids. Apart from all these, the solid CNF backbone helps the hybrid material to display excellent cycle stability with >98% retention in capacitance over 4500 charge-discharge cycles compared to pristine PEDOT at a current density of 2 A g(-1).

3-Dimensionally self-assembled single crystalline platinum nanostructures on few-layer graphene as an efficient oxygen reduction electrocatalyst - Unni, SreeKuttan M.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (RSC Advances, 2013)
Here, we report for the first time the synthesis of a 3-D self-assembled single crystalline platinum nanostructure directly on the graphene surface (PtNAGE) without using any harmful structural directing agents. A slow reduction method is used to prepare the desired platinum morphology. Initial formation of platinum nanoparticles and their homogenous dispersion on the surface of graphene have been observed 10 h after the commencement of the reduction using formic acid as the reducing agent. From these initially deposited seed particles, the growth starts on the {111} facets along the < 111 > direction and the nanostructure formation is completed within 72 h of the commencement of the reaction. The individual assembly has a diameter of similar to 80 nm. PtNAGE shows superior electrocatalytic activity towards oxygen reduction compared to graphene supported platinum (PtGE) and commercial carbon supported platinum (PtC) catalysts. PtNAGE is less vulnerable to strong hydroxyl adsorption compared to PtC and PtGE. Specific activity and mass activity of the catalyst are high compared to PtC by a factor of 6.50 and 1.80, respectively, and 4.00 and 3.05, respectively, compared to PtGE. The limiting current density of PtNAGE is 1.28 and 1.20 times higher than PtGE and PtC, respectively. Kinetic analysis of PtNAGE shows that the oxygen reduction reaction follows first order kinetics involving a four electron transfer mechanism with the direct formation of water. In addition to this, it has been observed that PtNAGE also prevents surface area degradation better than the commercial platinised carbon under potential induced conditions.

Design of a high performance thin all-solid-state supercapacitor mimicking the active interface of its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2013)
Here we report an all-solid-state supercapacitor (ASSP) which closely mimics the electrode-electrolyte interface of its liquid-state counterpart by impregnating polyaniline (PANO-coated carbon paper with polyvinyl alcohol-H2SO4 (PVA-H2SO4) gel/plasticized polymer electrolyte. The well penetrated PVA-H2SO4 network along the porous carbon matrix essentially enhanced the electrode-electrolyte interface of the resulting device with a very low equivalent series resistance (ESR) of 1 Omega/cm(2) and established an interfacial structure very similar to a liquid electrolyte. The designed interface of the device was confirmed by cross-sectional elemental mapping and scanning electron microscopy (SEM) images. The PANI in the device displayed a specific capacitance of 647 F/g with an areal capacitance of 1 F/cm(2) at 0.5 A/g and a capacitance retention of 62% at 20 A/g. The above values are the highest among those reported for any solid-state-supercapacitor. The whole device, including the electrolyte, shows a capacitance of 12 F/g with a significantly low leakage current of 16 mu A(2). Apart from this, the device showed excellent stability for 10000 cycles with a coulombic efficiency of 100%. Energy density of the PANI in the device is 14.3 Wh/kg.
Keywords: all-solid-state; cyclic voltametry; impedance analysis; polyaniline; polyvinyl alcohol; supercapacitor

Redox-mediated synthesis of functionalised graphene: a strategy towards 2D multifunctional electrocatalysts for energy conversion applications - Unni, SreeKuttan M.; Bhange, Siddheshwar N.; Anothumakkool, Bihag; Kurungot, Sreekumar (ChemPlusChem, 2013)
A simple, one-step synthetic route for developing a two-dimensional multifunctional electrocatalyst is reported, by the functionalisation of graphene using oxidised ethylenedioxythiophene (O-EDOT). The mutually assisted redox reaction between graphene oxide (GO) and EDOT facilitates the reduction of GO to graphene with a concomitant deposition of O-EDOT on the surface of the graphene. The oxidised surface of GO catalyses the reaction without using an added reducing agent, so a controlled and uniform deposition of O-EDOT is ensured on the surface of graphene, which essentially prevents the restacking of the layers. UV/Visible, IR, Raman and X-ray photoelectron spectroscopy give valid evidence for the reduction and functionalisation of graphene sheets. The functional groups present on the surface of graphene are found to tune the physical and chemical properties of graphene. Consequently, the functionalised material displays enhanced electrocatalytic activity for the reduction of oxygen to water and I3- to I- relative to pristine graphene. These distinct property characteristics make the material a versatile cathode electrocatalyst for both alkaline anion-exchange membrane fuel cells and dye-sensitised solar cells.
Keywords: electrocatalysts; fuel cells; graphene; redox chemistry; solar cells

Layer-separated distribution of nitrogen doped graphene by wrapping on carbon nitride tetrapods for enhanced oxygen reduction reactions in acidic medium - Unni, SreeKuttan M.; Illathvalappil, Rajith; Gangadharan, Pranav K.; Bhange, Siddheshwar N.; Kurungot, Sreekumar (Chemical Communications, 2014)
Layer-separated 3D nitrogen doped graphene (NG) with an accessible interstitial surface and modulated activity characteristics for oxygen reduction in acidic medium could be prepared by wrapping NG sheets on in situ generated carbon nitride (CNx) tetrapods.

Synthesis of an efficient heteroatom-doped carbon electro-catalyst for oxygen reduction reaction by pyrolysis of protein-rich pulse flour cooked with SiO2 nanoparticles - Gokhale, Rohan; Unni, SreeKuttan M.; Puthusseri, Dhanya; Kurungot, Sreekumar; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2014)
Development of a highly durable, fuel-tolerant, metal-free electro-catalyst for oxygen reduction reaction (ORR) is essential for robust and cost-effective Anion Exchange Membrane Fuel Cells (AEMFCs). Herein, we report the development of a nitrogen-doped (N-doped) hierarchically porous carbon-based efficient ORR electrocatalyst from protein-rich pulses. The process involves 3D silica nanoparticle templating of the pulse flour(s) followed by their double pyrolysis. The detailed experiments are performed on gram flour (derived from chickpeas) without any in situ/ex situ addition of dopants. The N-doped porous carbon thus generated shows remarkable electrocatalytic activity towards ORR in the alkaline medium. The oxygen reduction on this material follows the desired 4-electron transfer mechanism involving the direct reduction pathway. Additionally, the synthesized carbon catalyst also exhibits good electrochemical stability and fuel tolerance. The results are also obtained and compared with the case of soybean flour having higher nitrogen content to highlight the significance of different parameters in the ORR catalyst performance.

Two-in-one: inherent anhydrous and water-assisted high proton conduction in a 3D metal-organic framework - Nagarkar, Sanjog S.; Unni, SreeKuttan M.; Sharma, Amitosh; Kurungot, Sreekumar; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2014)
The development of solid-state proton-conducting materials with high conductivity that operate under both anhydrous and humidified conditions is currently of great interest in fuel-cell technology. A 3Dmetal-organic framework (MOF) with acid-base pairs in its coordination space that efficiently conducts protons under both anhydrous and humid conditions has now been developed. The anhydrous proton conductivity for this MOF is among the highest values that have been reported for MOF materials, whereas its water-assisted proton conductivity is comparable to that of the organic polymer Nafion, which is currently used for practical applications. Unlike other MOFs, which conduct protons either under anhydrous or humid conditions, this compound should represent a considerable advance in the development of efficient solid-state proton-conducting materials that work under both anhydrous and humid conditions.
Keywords: conducting materials; fuel cells; metal-organic frameworks; porous materials; proton conduction

Carbon nanohorn-derived graphene nanotubes as a platinum-free fuel cell cathode - Unni, SreeKuttan M.; Illathvalappil, Rajith; Bhange, Siddheshwar N.; Puthenpediakkal, Hasna; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
Current low-temperature fuel cell research mainly focuses on the development of efficient nonprecious electrocatalysts for the reduction of dioxygen molecule due to the reasons like exorbitant cost and scarcity of the current state-of-the-art Pt-based catalysts. As a potential alternative to such costly electrocatalysts, we report here the preparation of an efficient graphene nanotube based oxygen reduction electrocatalyst which has been derived from single walled nanohorns, comprising a thin layer of graphene nanotubes and encapsulated iron oxide nanopartides (FeGNT). FeGNT shows a surface area of 750 m(2)/g, which is the highest ever reported among the metal encapsulated nanotubes. Moreover, the graphene protected iron oxide nanoparticles assist the system to attain efficient distribution of Fe-N-x and quaternary nitrogen based active reaction centers, which provides better activity and stability toward the oxygen reduction reaction (ORR) in acidic as well as alkaline conditions. Single cell performance of a proton exchange membrane fuel cell by using FeGNT as the cathode catalyst delivered a maximum power density of 200 mW cm(-2) with Nafion as the proton exchange membrane at 60 degrees C. The facile synthesis strategy with iron oxide encapsulated graphitic carbon morphology opens up a new horizon of hope toward developing Pt-free fuel cells and metal-air batteries along with its applicability in other energy conversion and storage devices.
Keywords: carbon nanohorns; carbon nanotube; electrocatalyst; fuel cell; oxygen reduction reaction

CoSe2 supported on nitrogen-doped carbon nanohorns as a methanol-tolerant cathode for air-breathing microlaminar flow fuel cells - Unni, SreeKuttan M.; Mora-Hernandez, Juan M.; Kurungot, Sreekumar; Alonso-Vante, Nicolas (Chemelectrochem, 2015)
The synthesis of CoSe2 nanoparticles supported on nitrogendoped carbon nanohorns (CoSe2/NCNH) and the influence of the interaction of the metal centre with the NCNH on the oxygen reduction reaction (ORR) are reported. CoSe2/NCNH shows a 50 mV lower onset overpotential and a 150 mV positive shift in the half-wave potential compared to CoSe2 supported on carbon and carbon nanohorns. This suggests that the intrinsic activity and the density of active reaction centres of CoSe2 are modified by NCNHs. An air-breathing direct meth-anol microlaminar flow fuel cell (mLFFC) is constructed using CoSe2/NCNH as a methanol-tolerant cathode catalyst. A maximum power density of 10.05 mWcm(-2) and a maximum current density of 124.20 mAcm(-2) are achieved with CoSe2/NCNH compared to the non-doped catalyst, CoSe2/C and Pt/C with 5m methanol as the fuel. The improved activity of CoSe2/ NCNH is attributed to the peculiar morphology and the nitrogen doping of the carbon nanohorns. This catalyst could be a suitable alternative to Pt.
Keywords: carbon nanohorns; chalcogenides; fuel cells; oxygen reduction reaction; platinum

Layer-separated MoS2 bearing reduced graphene oxide formed by an in situ intercalation-cum-anchoring route mediated by Co(OH)(2) as a Pt-free electrocatalyst for oxygen reduction - Illathvalappil, Rajith; Unni, SreeKuttan M.; Kurungot, Sreekumar (Nanoscale, 2015)
A significant improvement in the electrochemical oxygen reduction reaction (ORR) activity of molybdenum sulphide (MoS2) could be accomplished by its layer separated dispersion on graphene mediated by cobalt hydroxide (Co(OH)(2)) through a hydrothermal process (Co(OH)(2)-MoS2/rGO). The activity make-over in this case is found to be originated from a controlled interplay of the favourable modulations achieved in terms of electrical conductivity, more exposure of the edge planes of MoS2 and a promotional role played by the coexistence of Co(OH)(2) in the proximity of MoS2. Co(OH)(2)-MoS2/rGO displays an oxygen reduction onset potential of 0.855 V and a half wave potential (E-1/2) of 0.731 V vs. RHE in 0.1 M KOH solution, which are much higher than those of the corresponding values (0.708 and 0.349 V, respectively) displayed by the as synthesized pristine MoS2 (P-MoS2) under identical experimental conditions. The Tafel slope corresponding to oxygen reduction for Co(OH)(2)-MoS2/rGO is estimated to be 63 mV dec(-1) compared to 68 mV dec(-1) displayed by the state-of-the-art Pt/C catalyst. The estimated number of electrons transferred during oxygen reduction for Co(OH)(2)-MoS2/rGO is in the range of 3.2-3.6 in the potential range of 0.77 V to 0.07 V, which again stands out as valid evidence on the much favourable mode of oxygen reduction accomplished by the system compared to its pristine counterpart. Overall, the present study, thus, demonstrates a viable strategy of tackling the inherent limitations, such as low electrical conductivity and limited access to the active sites, faced by the layered structures like MoS2 to position them among the group of potential Pt-free electrocatalysts for oxygen reduction.

Nitrogen-induced surface area and conductivity modulation of carbon nanohorn and its function as an efficient metal-free oxygen reduction electrocatalyst for anion-exchange membrane fuel cells - Unni, SreeKuttan M.; Bhange, Siddheshwar N.; Illathvalappil, Rajith; Mutneja, Nisha; Patil, Kasinath R.; Kurungot, Sreekumar (SMALL, 2015)
Nitrogen-doped carbon morphologies have been proven to be better alternatives to Pt in polymer-electrolyte membrane (PEM) fuel cells. However, efficient modulation of the active sites by the simultaneous escalation of the porosity and nitrogen doping, without affecting the intrinsic electrical conductivity, still remains to be solved. Here, a simple strategy is reported to solve this issue by treating single-walled carbon nanohorn (SWCNH) with urea at 800 degrees C. The resulting nitrogen-doped carbon nanohorn shows a high surface area of 1836 m(2) g(-1) along with an increased electron conductivity, which are the pre-requisites of an electro catalyst. The nitrogen-doped nanohorn annealed at 800 degrees C (N-800) also shows a high oxygen reduction activity (ORR). Because of the high weight percentage of pyridinic nitrogen coordination in N-800, the present catalyst shows a clear 4-electron reduction pathway at only 50 mV overpotential and 16 mV negative shift in the half-wave potential for ORR compared to Pt/C along with a high fuel selectivity and electrochemical stability. More importantly, a membrane electrode assembly (MEA) based on N-800 provides a maximum power density of 30 mW cm(-2) under anion-exchange membrane fuel cell (AEMFC) testing conditions. Thus, with its remarkable set of physical and electrochemical properties, this material has the potential to perform as an efficient Pt-free electrode for AEMFCs.

Surface-modified single wall carbon nanohorn as an effective electrocatalyst for platinum-free fuel cell cathodes - Unni, SreeKuttan M.; Ramadas, Sarath; Illathvalappil, Rajith; Bhange, Siddheshwar N.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2015)
Platinum (Pt) and its alloys are routinely used in the cathodes of polymer electrolyte membrane fuel cells (PEMFCs) due to their high electrocatalytic activity in oxygen reduction reactions (ORRs). A variety of alternative materials have been examined as alternatives to Pt, but most of these had low activity and their performance deteriorated even further in use. In the present study an alternate electrocatalyst has been examined, obtained by a simple surface modification of single-walled carbon nanohorns by simultaneous doping with Fe and N at 900 degrees C (FeNCNH-900). This had an ORR activity superior to that of 40 wt% Pt on carbon (Pt/C). Compared to Pt/C, FeNCNH-900 gave a 30 mV improvement in onset potential and a 20 mV gain in half-wave potential in an ORR. Its high activity is the result of the simultaneous modulation achieved by the high surface area and the microporosity of carbon nanohorns, together with the establishment of the desired nitrogen-iron coordinated pyrrolic active centres. The catalyst showed excellent electrochemical stability and, most notably, its ORR activity was still increasing after 1000 cycles. Single-cell fuel cell performance using FeNCNH-900 as cathode catalyst showed a maximum power density of 35 mW cm(-2) under alkaline conditions.

Nitrogen and sulphur co-doped crumbled graphene for the oxygen reduction reaction with improved activity and stability in acidic medium - Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2016)
Non-precious dioxygen reduction electrocatalysts have attracted great attention nowadays for the development of stable, cost-effective proton exchange membrane fuel cells. In line with the development of non-precious electrocatalysts, here we report the synthesis of a platinum-free oxygen reduction electrocatalyst based on nitrogen and sulphur co-doped crumbled graphene with trace amounts of iron. The co-doped crumbled graphene structure was obtained by simple oxidative polymerisation of ethylenedioxythiophene in aqueous solution followed by an annealing process under an inert atmosphere. This new electrocatalyst displays improved oxygen reduction activity and electrochemical stability under acidic conditions. The half-cell reaction of the 1000 degrees C annealed polyethylenedioxythiophene (PF-1000) displays only 0.1 V overpotential in both the onset and half-wave potentials compared to state-of-the-art Pt/C in an acidic environment for the ORR. More importantly, the limiting current of PF-1000 clearly surpasses the limiting current displayed by Pt/C, indicating that the crumbled assembly of the graphene flakes helps the system to expose the active sites and the porous network of the material matrix ensures extended accessibility of active sites to the electrolyte and reagent. The dioxygen reduction kinetics of PF-1000 appear similar to those of Pt/C and the system accomplishes the reduction of the dioxygen molecule through the recommended four-electron reduction pathway. The improved activity and electrochemical stability of PF-1000 are mainly attributed to the enriched and well accessible active reaction centres such as graphitic nitrogen, sulphur, and iron coordination and the peculiar morphology of PF-1000. Further, a single cell evaluation of a membrane electrode assembly based on PF-1000 as the cathode catalyst delivered a maximum power density of 193 mW cm(-2) at a cell temperature of 60 degrees C using Nafion as the proton conducting membrane.

Valorization of coffee bean waste: a coffee bean waste derived multifunctional catalyst for photocatalytic hydrogen production and electrocatalytic oxygen reduction reactions - Unni, SreeKuttan M.; George, Leena; Bhange, Siddheshwar N.; Devi, R. Nandini; Kurungot, Sreekumar (RSC Advances, 2016)
Here, we report the valorization of coffee bean waste (CBW) by producing nitrogen doped porous carbon (p-Cof) having both photocatalytic and electrocatalytic properties using a silica templating method. Morphological investigation of p-Cof reveals the presence of assemblies of highly porous flat carbon blocks. p-Cof exhibits a high surface area (1213 m(2) g(-1)) and a wide range of micro-and mesopores with good electrical conductivity. Along with this, the surface of p-Cof displays the presence of graphitic and pyridone-type nitrogen coordinations, which help p-Cof to perform as a multifunctional catalyst as revealed from its catalytic activities towards photocatalytic hydrogen production (PHP) and electrocatalytic oxygen reduction reactions. p-Cof produces 334 mu mol h(-1) g(-1) of hydrogen from water under visible light and 575 mmol h(-1) g(-1) of hydrogen under solar light irradiation with excellent stability. Along with this, p-Cof also displays improved oxygen reduction reaction (ORR) activity in alkaline medium. A better onset potential (0.91 V vs. RHE) and half-wave potential (0.75 V vs. RHE) are displayed by p-Cof compared to the catalyst derived from the simple annealing of CBW without employing the silica template. Along with the better electrochemical activity, p-Cof shows excellent ORR kinetics and electrochemical stability compared to the current state-of-the-art Pt/C.

Vitro and in silico antifungal efficacy of nitrogen- doped carbon nanohorn ( NCNH) against rhizoctonia solani - Dharni, Seema; Sanchita; Unni, SreeKuttan M.; Kurungot, Sreekumar; Samad, Abdul; Sharma, Ashok; Patra, Dharani Dhar (Journal of Biomolecular Structure & Dynamics, 2016)
We have investigated in vitro antifungal efficiency of nitrogen-doped carbon nanohorn (NCNH) against Rhizoctonia solani (R. solani) plant pathogenic fungi. NCNH with size of 50-60nm and concentrations of 10, 50, 100, and 150gmL(-1) were used. The results showed that growth of fungi in the presence of NCNH was significantly (p>.05) inhibited at 150gmL(-1) (85.13 +/-.97) after 72h. The results were validated through computational approaches. Molecular docking analysis of NCNH with endochitinase protein of R. solani was performed to validate the potential of antifungal activity of NCNH. Docking results showed different conformations of interaction of NCNH with endochitinase enzyme. The conformation with least binding energy -13.54kcal/mol was considered further. It is likely that NCNH interacts with the pathogens by mechanically wrapping, which may be one of the major toxicity actions of NCNH against R. solani. The analysis showed that NCNH might interwinds to endochitinase of R. solani leading to the deactivation of the enzyme. To best of our knowledge, this is the first report of antifungal efficacy of NCNH against R. solani and provides useful information about the application of NCNH in resisting crop disease.
Keywords: docking; endochitinase; nitrogen-doped carbon nanohorn; Rhizoctonia solani

In situ grown nickel nanoparticles in a calixarene nanoreactor on a graphene-MoS2 support for efficient water electrolysis - Waghmode, Babasaheb J.; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Patil, Kashinath R.; Malkhede, Dipalee D. (Sustainable Energy & Fuels, 2017)
Electrochemical production of hydrogen, facilitated in electrolysers, holds great promise for energy storage and solar fuel production. Catalysis of the oxygen evolution reaction (OER) is a bottleneck of this process. However, the sluggish OER kinetics and the utilization of precious metal catalysts are key obstacles in the broad deployment of this energy technology. We report the preparation and use of an inexpensive GrMoS(2)SC(8)Ni nanocomposite material as a highly effective OER catalyst in an alkaline electrolyte. Experimental investigations have shown that improvements can be realized in the catalytic performance of Ni metal if it is a component of the composite material. We propose an explanation for these enhancements based on a hydrogen acceptor concept. This concept comprises the stabilization of an *-OOH intermediate, which effectively lowers the potential needed for breaking bonds on the surface. Herein, an inexpensive immobilized SC8 layer was used as the nanoreactor to synthesize metallic Ni nanoparticles (NPs) through an in situ redox process. The process was applied to form immobilized NPs on flat and curved 2D surfaces. The outstanding OER performance of Ni NPs could be attributed to their large surface area, efficient mass and charge transport, and high structural stability arising from the unique SC8 cage structure, built on the GrMoS(2) substrate. The GrMoS(2)SC(8)Ni nanocomposite shows the highest activity, exhibiting a 214 mV overpotential at 10 mA cm(-2) (equivalent to 10% efficiency of solarto-fuel conversion) and a Tafel slope of 31 mV dec(-1) in 1 M KOH solution. It further demonstrates high stability as there is no apparent OER activity loss (based on a chronoamperometry test) or particle aggregation (based on SEM image observation) after a 10 h anodization test. The facile preparation method and high efficiency and durability enable this electrocatalyst to be a promising candidate for future large-scale applications in water splitting. Thus, this work opens a new avenue toward the development of highly efficient, inexpensive OER catalysts.

Nitrogen-doped graphene with a three-dimensional architecture assisted by carbon nitride tetrapods as an efficient metal-free electrocatalyst for hydrogen evolution - Gangadharan, Pranav K.; Unni, SreeKuttan M.; Kumar, Nandha; Ghosh, Prasenjit; Kurungot, Sreekumar (Chemelectrochem, 2017)
Current polymer membrane-based electrolyzers use Pt as a cathode catalyst for efficient reduction of water. The high cost of Pt-based catalysts forces researchers to develop alternative electrocatalysts. Here, a simple strategy has been proposed to synthesize a metal-free electrocatalyst for the hydrogen evolution reaction (HER) by high-temperature annealing of graphene oxide-coated melamine foam. The prepared catalyst possesses both structural and functional advantages with its three-dimensional (3D) interconnected arms of carbon nitride (CNx) backbone wrapped with nitrogen-doped graphene (N-RGO) sheets (CNx@N-RGO). CNx@N-RGO faces only a 193 mV overpotential to achieve a current density of 10mAcm(-2), which is far superior to the previously reported Pt-free systems. Along with the high exchange current density 34.7 x 10(-6)A cm(-2) and low Tafel slope of 54 mV dec(-1), CNx@N-RGO follows a Volmer-Heyrovsky mechanism for the HER. DFT calculations show that the synergy between CNx and N-RGO facilitates good electrical coupling between the two moieties and provides optimal binding to H+ ions on the catalyst that, in turn, results in efficient reduction of hydrogen ions.
Keywords: carbon nitride; Density functional theory; electrocatalyst; hydrogen evolution reaction; nitrogen doped graphene

Functionalized single-walled carbon nanohorns to reinforce sulfonated poly(ether ether ketone) electrolyte for direct methanol fuel cells - Turanelloormana, Parameswaran; Sarmah, Sudeshna; Torris, Arun; Bhat, Santoshkumar D.; Unni, SreeKuttan M. (ChemElectroChem, 2020)
Carbon-nanomaterial-based additives are promising materials for improving the physicochemical properties of sulfonated polyether ether ketone (sPEEK) for its use as composite membrane electrolyte in direct methanol fuel cells (DMFCs). In this work, functionalized single-wall carbon nanohorns (f-SWNHs) are realized as an additive in sPEEK. The -COOH groups created on the SWNHs during peroxide treatment improve the dispersion of f-SWNHs in sPEEK and boost the proton conductivity, ion exchange capacity, mechanical properties and reduce the methanol permeability of the electrolyte. The composite membrane with 0.50 wt.% f-SWNHs shows improved electrochemical selectivity of 17.03x10(-4) Scm(-3)s and delivers the highest peak power density of 230 mW cm(-2)in DMFCs.
Keywords: carbon nanohorns; direct methanol fuel cells; membrane electrolyte; proton conductivity; sulfonated poly ether ether ketone